Pengaruh Keuangan Syariah terhadap Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia di Indonesia - Rika Yulita Amalia; Syifa Fauziah; Indah Wahyuningsih (AL-MUZARA'AH, 2019)
One of variable to calculate the Human Development Index (HDI) is a decent standard of living derived from the Gross Domestic Product (GDP) figure. Therefore, the increase in HDI could be influenced by GDP. Furthermore, as a Muslim-majority country and adopting a dual banking system, Indonesia's GDP is certainly also influenced by the Islāmic financial sector, such as zakat and Islāmic bank financing. In this case, zakat plays role as a wealth distribution instrument. Then Islamic bank financing could be a funding capital for the community and the country. So, this study analyzes the direct and indirect relationship between the variables of zakat, Islamic bank financing and GDP to the HDI. The method used is path analysis which aims to look at the hypothesis of causal relationships. The results obtained are the direct relationship of Islamic bank financing and GDP significantly positive effect on HDI. Zakat and Islamic bank financing variables have a positive effect on GDP. The greatest coefficient value between direct relationships is the coefficient of Islamic bank financing on GDP, which is equal to 81.7%. But the direct relationship of zakat to the HDI cannot be known. While the indirect relationship shows that there is an influence between the variables of zakat on the HDI through GDP and there is an influence between the variables of Islamic bank financing on the HDI through GDP.